A Competência Consultiva da Corte Interamericana de Direitos Humanos - Antônio Celso Alves Pereira (Revista Interdisciplinar de Direito, 2014)
This paper aims at analyzing the advisory jurisdiction of the Inter-American Court of Human Rights. Th is court conforms an independent and autonomous judicial institution whose purpose includes the application and interpretation of the American Convention on Human Rights .. Th e Court was established in 1979 and is headquartered in San Jose, Costa Rica. Its creation stems from the proposal presented by the Brazilian delegation to IXª Inter-American Conference held in Bogotá in 1948. Th e functions of the Court are classifi ed and defi ned by the American Convention in two categories: litigation, articles 61, 62 and 63, and advisory, Article 64. its extent, the advisory jurisdiction of the Court is presented in the context of international courts, as sui generis. Th roughout his fruitful activity, the Inter-American Court, in response to requests from Member States and the Inter-American Commission on Human Rights, edited Advisory Opinions which, for its originality, represent important contributions to the evolution of international human rights Law.